Simplify:

\(x^6 \times x^5\) =

\(x^6 \times x^5\) =

`______`

.Simplify:

\(x^6 \times x^5\) =

\(x^6 \times x^5\) =

`______`

.Detailed Explanation

Recall that the multiplication of terms sharing the same base can be simplified by adding the exponents:

\(x^a + x^b = x^{(a+b)} \)

If this rule is forgotten, you can quickly derive it by considering the simple case of \(2^1 2^2\) , which can be rewritten as \(2 \times 2 \times 2\), or \(2^3\). The expression in this case, then, can be simplified as: \(x^6 \times x^5 = x^{(6+5)} = x^{11}\)

\(x^a + x^b = x^{(a+b)} \)

If this rule is forgotten, you can quickly derive it by considering the simple case of \(2^1 2^2\) , which can be rewritten as \(2 \times 2 \times 2\), or \(2^3\). The expression in this case, then, can be simplified as: \(x^6 \times x^5 = x^{(6+5)} = x^{11}\)